Two new species of Parasaveljevia Wieser, 1953 (Thoracostomopsidae, Nematoda) from Argentinean coasts (Chubut, Argentina) - Pastor, Catalina; Russo, Virginia Lo; Villares, Gabriela (Zootaxa, 2015)
Two new Parasavaljevia species are described, one from Puerto Madryn, and one from El Límite beach, San Jorge Gulf, Chubut Province, Argentina. The two species are characterised by a combination of characters. Parasavaljevia uncinoa n. sp. is characterised by having a long rectangular cirrus, positioned at the level of the inner labial setae, rectangular mandibles with prominent lateral hooks bearing denticles in three lines of nine each, and six cephalic setae of the same length, inserted at the anterior end of a small head capsule. Parasavaljevia limitense n. sp. is characterized by having a cirrus posterior positioned, between the labial and cephalic setae, rectangular-arched mandibles bearing denticles in five lines of ten each in a gradient of sizes; a small buccal cavity, small cephalic capsule and abundant cervical setae (4+10). An emendation of the genus diagnosis and a new key are given and discussed.